2020
DOI: 10.32607/actanaturae.10941
|View full text |Cite
|
Sign up to set email alerts
|

The genome structure of ciprofloxacin-resistant Mycoplasma hominis clinical isolates

Abstract: The genome structure of three ciprofloxacin-resistant Mycoplasma hominis clinical isolates was studied using next-generation sequencing on the Illumina platform. The protein sequences of the studied Mycoplasma strains were found to have a high degree of homology. Mycoplasma hominis (M45, M57, MH1866) was shown to have limited biosynthetic capabilities, associated with the predominance of the genes encoding the proteins involved in catabolic processes. Multiple single-nucleotide substitutions causing intraspeci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…It has been suggested that the resistance of M. hominis to ciprofloxacin is the result of the efflux transporters of MATE family. There are only a few reports that such efflux pumps can transport macrolides (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the resistance of M. hominis to ciprofloxacin is the result of the efflux transporters of MATE family. There are only a few reports that such efflux pumps can transport macrolides (13,14).…”
Section: Introductionmentioning
confidence: 99%